Kandungan Pospor-tersedia Pada Berbagai Kondisi Lahan Yang Berbeda danProduktivitasKelapa Sawit (Elaeis guineensis Jacq.)Afdeling IV Rimsa PTPN VI Persero Rimbo Bujang Kabupaten Tebo Jambi - Nasamsir Nasamsir; Yulistiati Nengsih; Hadi Pranata Purba (Jurnal Media Pertanian, 2022)
This study aims to determine the content of available P in Ultisol soil with various land conditions and its relationship with oil palm productivity. The research was carried out at the Afdeling IV Rimsa PTPN VI Persero Oil Palm Plantation in Pematang Sapat Village, Rimbo Bujang District, Tebo Jambi Regency, and soil analysis in the Jambi BLHD laboratory. The plants used are 16 years old. The study was carried out from May to June 2021. The environmental design used was a 1 (one) factor randomized block design, with the treatment design being land conditions (k) consisting of: k1 = flat land (slope < 5%) , k2 = sloping land (slope >10 % ), and k3 = land that is inundated when it rains. Each treatment was repeated 3 times, so that 9 research units were obtained. Each research unit has 3 observation sample points so that the number of observation sample points is 27 points. Parameters observed include; P-available, Al–dd, Fe, pH, soil characteristics, and productivity of oil palm plants. Plant productivity data were analyzed by analysis of variance and continued with further test of DNMRT 5% and data of available P, Al–dd, Fe, pH, soil characteristics were analyzed descriptively and tabulated. The results showed that there were differences in soil texture, soil color, available P, Al–dd, Fe, and soil pH from the 3 observed land conditions. There were differences in oil palm productivity on slopes <5% (k1) (27,756 tons- 1ha-1th-1) with land productivity with a slope of > 10% (k2) which is 19,032 tons-1ha-1th-1. The productivity of oil palm land that is inundated when it rains (k3) is 30.804 tons-1ha-1th-1, which is not significantly different from land with a slope of <5%. Keywords: oil palm land, P-available